Negotiating the veil and identity in Leila Aboulela's Minaret - Al-Karawi, Susan Taha; Bahar, Ida Baizura (Penerbit Universiti Kebangsaan Malaysia, 2014)
Leila Aboulela’s novel, Minaret (2005), provides authentic and rich content to explore the Muslim Arab woman’s struggle over creating a modern yet religiously traditional identity. The conceptual framework of Victor Turner’s liminality and Homi Bhabha’s hybridity and the third space are applied in order to frame the analysis of this struggle and to show that the veil is a metaphor for the Arab woman’s positive and negative experiences. In Minaret, the protagonist, Najwa, experiences a sense of in-betweenness or liminality through crises, transitions, and resolutions of secular and religious lives. The different hybrid identities and efforts Najwa makes to come to terms with her developing Muslim identity is discussed, particularly through her and the women around her who choose to wear the veil and modest, rather than revealing, clothing. Together, these form our analysis of the Muslim Arab woman’s struggle to be Muslim through wearing the veil while living in Britain. The veil in this novel is furthermore symbolic of traditional Islamic culture and represents the struggle to be religiously faithful despite being surrounded by non-Muslims or non-practising Muslims. This then provides the means of understanding individual mobility, empowerment, and agency through which liminality is successfully negotiated in order to achieve a hybrid identity of Eastern and Western cultures.